Characterization of the intensity of effort of blind athletes from the Brazilian Football 5-A-Side national team - Souza, Ramon Pereira; Alves, José Manuel Vilaça Maio; Gorla, José Irineu; Novaes, Giovanni; Cabral, Soraia Izabel Correa; Neves, Eduardo Borba; Nogueira, Claudio Diehl (Journal of Health & Biological Sciences, 2016)
Introduction: Football 5-a-side is a sport played by blind athletes that takes part in the Paralympic Games since 2004. The Brazilian national team is currently considered the best team in the world in this sport. Objective: To analyze the variations of intensity of effort (average per position and group average) made by blind athletes of the Brazilian football 5-a-side national team during six matches simulations. Methods: The sample on this research is the intentional type, made with eight blind male players, ages ranging from 21 to 30 years old (23.8 ± 3.3), all of them part of the Brazilian Football 5-a-side National team, which played in the 2012 Paralympics Games in England. In was evaluated the VO2máx and the heart rate during six simulations of official matches. Results: The intensity of effort of the blind athletes of the Brazilian Football 5-a-side National Team is intermittent and remains 52.5 % of the total time of a match (50 minutes) with an intensity of effort between the zone 2 (between threshold ventilation and respiratory compensation point) and the zone 3 (above the respiratory compensation point) averaging 89.8 % of the HR max. Conclusion: The intensity of effort is greater than the Football of 11 and, that in the Futsal players.